Phosphorylation of estrogen receptor α at serine 118 is correlated with breast cancer resistance to tamoxifen - CHEN, MING (D.A. Spandidos, 2013)
The aim of the present study was to explore the correlation between estrogen receptor α (ERα) phosphorylation at serines 118 and 167 and the responsiveness of patients with primary breast cancer to tamoxifen. Tumors from 104 patients with primary breast cancer who received adjuvant tamoxifen therapy at The Affiliated Cancer Hospital of Shantou University Medical College between January 2001 to December 2007 were subjected to immunohistochemical analysis with specific antibodies against ERα phosphorylated at either serine 118 (pERα-S118) and/or serine 167 (pERα-S167). ERα phosphorylation at the two sites was correlated with either the disease-free survival or the overall survival rate of these patients using the Kaplan-Meier survival analysis. pERα-S118 and pERα-S167 were found to be expressed in the cell nucleus of 25.0% (26/104) and 26.9% (28/104) of breast cancers, respectively. The expression of pERα-S118 was positively correlated with the human epidermal growth factor receptor-2 (HER-2) status (χ(2)=6.85, P=0.01). The Kaplan-Meier analysis revealed a poorer disease-free (P=0.022) and overall survival (P=0.013) in breast cancer patients expressing pERα-S118, but not in those expressing pERα-S167. In conclusion, pERα-S118 was correlated with the HER-2 status and predicted breast cancer resistance to tamoxifen.